2020
DOI: 10.1371/journal.pone.0236649
|View full text |Cite
|
Sign up to set email alerts
|

Site-fidelity and spatial movements of western North Pacific gray whales on their summer range off Sakhalin, Russia

Abstract: The Western North-Pacific (WNP) gray whale feeding grounds are off the northeastern coast of Sakhalin Island, Russia and is comprised of a nearshore and offshore component that can be distinguished by both depth and location. Spatial movements of gray whales within their foraging grounds were examined based on 13 years of opportunistic vessel and shore-based photo-identification surveys. Site fidelity was assessed by examining annual return and resighting rates. Lagged Identification Rates (LIR) analyses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 70 publications
(142 reference statements)
1
17
0
Order By: Relevance
“…Western gray whales migrate over 10000 km to feed within a spatially small foraging ground off Sakhalin Island (Mate et al, 2015 ). Gray whales observed off Sakhalin have high site fidelity and annual return rate to the two known feeding areas (Bröker et al, 2020 ). Other foraging areas within the Sea of Okhotsk have not been identified to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Western gray whales migrate over 10000 km to feed within a spatially small foraging ground off Sakhalin Island (Mate et al, 2015 ). Gray whales observed off Sakhalin have high site fidelity and annual return rate to the two known feeding areas (Bröker et al, 2020 ). Other foraging areas within the Sea of Okhotsk have not been identified to date.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, mothers with calves have never been observed in the offshore area during the weaning period. Younger individuals (< 5 years of age) also tend to have a higher affinity for the nearshore feeding area (Bröker et al, 2020 ; Schwarz et al, 2022a ). However, the amphipod-rich offshore feeding area (Blanchard et al, 2019 ; Demchenko et al, 2016 ) may be critical for pregnant females (McHuron et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Their two known feeding areas are small compared to that of eastern gray whales and many other baleen whales (Mate et al, 2011;Moore et al, 2003), and they exhibit a high degree of site fidelity to these areas (Fig. 1) (Bröker et al, 2020). In addition, the estimated population size is small for a K-selected species, with 175 identified non-calf individuals, of which 33 are known reproducing females (Cooke et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In 1995, concern for the potential impact of such activities on gray whales feeding off SI led to the initiation of a long-term monitoring effort by Russian and U.S. scientists (Weller et al, 1999). Photo-identification data collected as part of these efforts, which have been conducted annually since 1997 and continue to date as part of the Russian Gray Whale Project, as well as data collected by industry-funded efforts since 2002, indicate that a small number of whales demonstrate strong fidelity to this feeding area both within and between years (Bradford, 2011;Bradford et al, 2008;Bröker et al, 2020;Burdin et al, 2020;Weller et al, 1999Weller et al, , 2002b). Use of the SI feeding ground is driven in part by matrilineal fidelity, as many of the whales first identified as calves with their mothers have been sighted on the SI feeding ground in subsequent seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, WNP whales were presumed to feed only off the coast of SI, in a nearshore and an offshore area (Bröker et al, 2020;Meier et al, 2007;Weller et al, 2002aWeller et al, , 2003. However, photo-identification studies off southern and eastern Kamchatka indicated that approximately half of the whales identified in that region are whales known to use the SI feeding ground (Burdin et al, 2011;Tyurneva et al, 2010;Vertyankin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%